Kinetic evaluation of the Arrhenius equation for artificial ageing of polymers - Lázaro, David (2025)
Artificial ageing of polymers is a crucial and complex issue, especially considering that critical infrastructures such as nuclear power plants have lifespans varying from 40 to 60 years or even longer. Controlled artificial ageing allows the evaluation of polymer lifetimes while ensuring that their properties are preserved. However, a unified and validated methodology for artificially ageing polymers is still lacking. One of the most extended methodologies for the artificial ageing of polymers is the Arrhenius methodology. This methodology is based on the application of the Arrhenius equation, which is extensively applied in the study of thermal decomposition reactions. Nevertheless, the Arrhenius methodology requires the estimation of activation energy, and the lack of a unified method introduces variability in results obtained using different methods. Furthermore, the Arrhenius ageing methodology assumes that the kinetic parameters do not change during ageing, meaning that aged and non-aged materials should exhibit the same activation energy. The present work aims to analyse the hypothesis of unvariable activation energy during ageing. This was investigated using both new and artificially aged PVC samples, evaluating the activation energy through various mathematical models based on thermogravimetric analysis.